Burden of Giardia duodenalis infection and its adverse effects on growth of schoolchildren in rural Malaysia. - Hesham M Al-Mekhlafi; Mohamed T Al-Maktari; Rohana Jani; Abdulhamid Ahmed; Tengku Shahrul Anuar; Norhayati Moktar; Mohammed A K Mahdy; Yvonne A L Lim; Rohela Mahmud; Johari Surin (Public Library of Science (PLoS), 2013)
BACKGROUND: Giardia duodenalis infection and malnutrition are still considered as public health problems in many developing countries especially among children in rural communities. This study was carried out among Aboriginal (Orang Asli) primary schoolchildren in rural peninsular Malaysia to investigate the burden and the effects of Giardia infection on growth (weight and height) of the children. METHODS/FINDINGS: Weight and height of 374 children aged 7-12 years were assessed before and after treatment of Giardia infection. The children were screened for Giardia parasite using trichrome staining technique. Demographic and socioeconomic data were collected via face-to-face interviews using a pre-tested questionnaire. Overall, 22.2% (83/374) of the children were found to be infected with Giardia. Nutritional status of children was assessed and the results showed that the mean weight and height were 23.9 kg (95% CI = 23.3, 24.5) and 126.6 cm (95% CI = 125.6, 127.5), respectively. Overall, the prevalence of severe underweight, stunting and wasting were 28.3%, 23.8% and 21.0%, respectively. Multiple linear regression analyses showed sex, Giardia infection and household monthly income as the significant determinants of weight while sex and level of mother's education were the significant determinants of height. Weight and height were assessed at 3 and 6 months after treatment of Giardia infection. It was found that Giardia infection has a significant association with the weight of children but not with height. CONCLUSIONS/SIGNIFICANCE: This study reveals high prevalence of Giardia infection and malnutrition among Aboriginal children in rural Malaysia and clearly highlights an urgent need to identify integrated measures to control these health problems in the rural communities. Essentially, proper attention should be given to the control of Giardia infection in Aboriginal communities as this constitutes one of the strategies to improve the nutritional status of Aboriginal children.